Liposomes loaded with vitamin D3 induce regulatory circuits in human dendritic cells - Nagy, Noémi Anna; Lozano Vigario, Fernando; Sparrius, Rinske; van Capel, Toni M. M.; van Ree, Ronald; Tas, Sander W.; de Vries, I. Jolanda M.; Geijtenbeek, Teunis B. H.; Slütter, Bram; de Jong, Esther C., for the DC4Balance consortium (Frontiers in Immunology, 2023)
Introduction Nanomedicine provides a promising platform for manipulating dendritic cells (DCs) and the ensuing adaptive immune response. For the induction of regulatory responses, DCs can be targeted in vivo with nanoparticles incorporating tolerogenic adjuvants and auto-antigens or allergens. Methods Here, we investigated the tolerogenic effect of different liposome formulations loaded with vitamin D3 (VD3). We extensively phenotyped monocyte-derived DCs (moDCs) and skin DCs and assessed DC-induced regulatory CD4+ T cells in coculture. Results Liposomal VD3 primed-moDCs induced the development of regulatory CD4+ T cells (Tregs) that inhibited bystander memory T cell proliferation. Induced Tregs were of the FoxP3+ CD127low phenotype, also expressing TIGIT. Additionally, liposome-VD3 primed moDCs inhibited the development of T helper 1 (Th1) and T helper 17 (Th17) cells. Skin injection of VD3 liposomes selectively stimulated the migration of CD14+ skin DCs. Discussion These results suggest that nanoparticulate VD3 is a tolerogenic tool for DC-mediated induction of regulatory T cell responses.